2015
DOI: 10.1111/ggi.12575
|View full text |Cite
|
Sign up to set email alerts
|

Influence of comorbidities on the efficacy of pulmonary rehabilitation in patients with chronic obstructive pulmonary disease

Abstract: PR is equally effective in elderly and younger patients with COPD, with efficacy influenced by body mass index and anxiety. Geriatr Gerontol Int 2016; 16: 934-941.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
0
14
3
Order By: Relevance
“…reported that the level of daily PAL is impaired by the presence of comorbidities, irrespective of the types of comorbidity . We previously showed that these comorbidities influence the efficacy of PR, as measured by 6MWD and SGRQ . However, in the present study, the changes in PAL were not associated with individual comorbidities or comorbidity indexes.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…reported that the level of daily PAL is impaired by the presence of comorbidities, irrespective of the types of comorbidity . We previously showed that these comorbidities influence the efficacy of PR, as measured by 6MWD and SGRQ . However, in the present study, the changes in PAL were not associated with individual comorbidities or comorbidity indexes.…”
Section: Discussioncontrasting
confidence: 84%
“…A recent review reported that up to 40% of patients with COPD have symptoms of depression or anxiety, and the prevalence can be higher among patients with advanced disease and those using supplemental oxygen . The depression score was not improved by PR in the present study nor in our previous cohort study with a larger number of patients . Most of the previous studies showed that PR improved depression and anxiety scores, although some studies showed the depression score did not change after PR .…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations